Physiological and Biochemical Characterization for Drought Stress at Seedling Stage in Wheat Genotypes - Zala, Harshvardhan N.; Bosamia, Tejas C.; Kulkarni, Kalyani S.; Shukla, Yogesh M. (International Journal of Bio-resource and Stress Management, 2023)
A laboratory experiment was conducted to evaluate the cultivated wheat genotypes of middle Gujarat region for tolerance to drought, artificially created by the application of 0, 5, and 10% polyethylene glycol (PEG). During screening, data were recorded for various physiological and biochemical parameters of the wheat genotypes. Decrease in percent germination was observed with the increase in the level of PEG at 5% and 10% in all the genotypes. However, percent germination was significantly higher in the genotypes LOK 1, HW-2004, AR-06-1, AR-07-33, AR-07-30 and GW-1 reflecting the drought tolerance characteristics. Overall, with increased concentration of artificial drought stress inducer, PEG, reduction in germination percentage, root length, shoot length and seedling vigor index was observed. Proline content increased during stress condition induced by 5% and 10% PEG. Isozymes study of peroxidase, catalase under normal and drought stress conditions showed specific banding pattern which appeared only after PEG induce stress where as esterase showed unaltered banding pattern. The study of protein banding pattern through SDS-PAGE identified induced proteins involved in drought stress response. The protein bands of 158 kDa and 196 kDa were induced under the 5% and 10% PEG concentrations, respectively. From this primary screening, the wheat genotypes were characterized on the basis of response to PEG induced drought. Among all the irrigated aestivum genotypes, LOK-1, HW-2004 were found to be highly tolerant while the genotypes, GW-496, GW-173 and GW-322 were moderately susceptible and the genotypes, GW-273, GW-366 were found to be highly drought susceptible. Among the durum genotypes, rainfed genotypes A-206, DR-08-07, AR-06-1, A-9-30-1, AR-07-7, AR-07-30, AR-07-33and DR-08-06 were highly tolerant. Among the irrigated genotypes of durum wheat, GW-1245, GW-1255, GW-1260, GW-1265 and HI-8498 were moderately susceptible whereas GW-1139 was found to be highly drought susceptible.